Typing of Pneumocystis carinii strains that infect humans based on nucleotide sequence variations of internal transcribed spacers of rRNA genes. - Lu, J J (1994)
Small portions of the 18S and the 26S rRNA genes, the entire 5.8S rRNA gene, and internal transcribed spacers ITS1 and ITS2 (located between the 18S and 5.8S rRNA genes and between the 5.8S and 26S rRNA genes, respectively) of Pneumocystis carinii that infect humans were cloned and sequenced. The nucleotide sequences of the 18S, 5.8S, and 26S rRNA genes determined in the study were approximately 90% homologous to those of P. carinii that infect rats, while the sequences of ITS1 and ITS2 of P. carinii from the two different hosts were only 60% homologous. The 18S, 5.8S, and 26S rRNA gene sequences of P. carinii from 15 patient specimens were determined and were found to be identical to each other, whereas the ITS sequences were found to be variable. With the observed sequence variation, it was possible to classify the ITS1 sequences into two types and the ITS2 sequences into three types. P. carinii strains that had the same type of ITS1 sequence could have a different type of ITS2 sequence. On the basis of the sequence types of the two ITS regions, P. carinii from the 15 patients were classified into four groups. P. carinii from three patient specimens were found to contain two different ITS sequence patterns. More surprisingly, one additional specimen was found to have one ITS sequence typical of P. carinii isolates that infect humans and another typical of P. carinii isolates that infect rats. The studies indicate that it is possible to type P. carinii strains on the basis from one patient, suggesting that coinfection with more than one strain of P. carinii may occur in the same patient.